Taking the Big Leap: A Case Study on Implementing Programmatic Assessment in an Undergraduate Medical Program - Raphaël Bonvin; Elke Bayha; Amélie Gremaud; Pierre-Alain Blanc; Sabine Morand; Isabelle Charrière; Marco Mancinetti (MDPI AG, 2022)
The concept of programmatic assessment (PA) is well described in the literature; however, studies on implementing and operationalizing this systemic assessment approach are lacking. The present case study developed a local instantiation of PA, referred to as Assessment System Fribourg (ASF), which was inspired by an existing program. ASF was utilized for a new competency-based undergraduate Master of Medicine program at the State University of Fribourg. ASF relies on the interplay of four key principles and nine main program elements based on concepts of PA, formative assessment, and evaluative judgment. We started our journey in 2019 with the first cohort of 40 students who graduated in 2022. This paper describes our journey implementing ASF, including the enabling factors and hindrances that we encountered, and reflects on our experience and the path that is still in front of us. This case illustrates one possibility for implementing PA.